Pengaruh Bantuan Operasional Sekolah terhadap Pemenuhan Akses Pendidikan Menengah di Indonesia - Sitanggang, Desmawan Anselmus; Jasmina, Thia (Direktorat Jenderal Perbendaharaan, Kementerian Keuangan, 2023)
Since 2013, the Indonesian government has established the Universal Secondary Education (PMU) program or 12-year compulsory education. In line with the program, the central government transfers School Operational Assistance (BOS) funds to formal secondary schools, which is expected to free or lower the school fees. However, until 2019, the Net Enrollment Rate (NER) for secondary education did not reach the target set in the 2015-2019 strategic plan. It is estimated that around 3.2 million children aged 16-18 are out of school, which indicates that there are barriers to accessing secondary education in Indonesia, especially school fees. This study aims to analyze the effect of BOS on the fulfillment of access to secondary education in Indonesia as measured by changes in the NER for Senior High Schools (SMA) and Vocational High Schools (SMK). Since 2017, the authority of SMA and SMK in Indonesia has been decentralized to the provincial government. This study applies the Fixed Effect estimation method to panel data of 34 provinces in Indonesia from 2017 to 2021. The estimation results show that SMA/SMK BOS does not affect changes in the NER of SMA/SMK. This result is, among others, due to a relatively small amount of BOS funds compared to the operational costs of secondary schools and the weak accountability of local government for managing BOS funds. Therefore, the government needs to allocate more educational budget, especially for secondary schools, and intensively monitor and evaluate the use of BOS funds and other education budgets.